RANCANG BANGUN APLIKASI PENDUKUNG PELAKSANAAN AUDIT SISTEM VERIFIKASI LEGALITAS KAYU (SVLK) BERBASIS WEBSITE (Science and Technology (SciTech), 2023)
The purpose of the audit is to verify that the subject matter of the audit has been completed and is running according to the specified standards. The application of an audit in this case is related to an audit of the Timber Legality Assurance System (SVLK) to evaluate and verify a company and ensure the legitimacy of timber legality. The audit process still does not fully use a computerized system and is still manual. The audit team must collect documents one by one according to the check list to find the desired data. Therefore, an application was made, namely the website-based SVLK Audit System, which can help the audit process be more effective and efficient. The method used is Rapid Application Development (RAD), which is a software development method with short phases and PHP as the programming language used. All parties involved in the audit, namely the audited company and the auditing institution, do not need to use a lot of paper and take a long time so that the audit is more effective and efficient, and data can be processed easily and quickly so that the data is more organized.